2011
DOI: 10.1093/rheumatology/ker307
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus risk factors for coronary artery calcifications

Abstract: Disease activity is a potentially modifiable risk factor for coronary artery calcifications in SLE. Therefore, management of traditional risk factors plus tight control of lupus activity, including the use of anti-malarials, is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 31 publications
6
51
0
2
Order By: Relevance
“…Several other studies have failed to show an association of SLE disease activity with subclinical measures of atherosclerosis 38,39,40 . A recent study of 139 patients with SLE found that a longer period with moderate to severe activity (as measured by SLEDAI) was associated with coronary artery calcium 41 . A Canadian study also found that disease activity as measured by SLEDAI was associated with risk for coronary artery disease 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have failed to show an association of SLE disease activity with subclinical measures of atherosclerosis 38,39,40 . A recent study of 139 patients with SLE found that a longer period with moderate to severe activity (as measured by SLEDAI) was associated with coronary artery calcium 41 . A Canadian study also found that disease activity as measured by SLEDAI was associated with risk for coronary artery disease 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Silent myocardial infarction has been also diagnosed by myocardial perfusion SPECT in SLE [43] . Additionally, abnormal perfusion was identified in asymptomatic, factor [55] . Finally, another CT study demonstrated that the calcification of cardiac valves is more prevalent in RA and SLE, compared with controls.…”
Section: Single-photon Emission Computed Tomographymentioning
confidence: 95%
“…One inception cohort study found no association between disease activity (measured using SLEDAI-2K) and cardiovascular events [27], while several other studies found that higher SLEDAI scores did predict MI and /or stroke [2830]. Similarly, although one study found that higher mean disease activity scores were significantly associated with subclinical atherosclerosis (increased coronary calcium scores) [31]; Manzi et al found an inverse relationship between SLE activity and carotid plaque [32], while several other studies found no association between disease activity and progression of atherosclerosis [3335]. Renal disease activity also appears to be a risk factor for atherosclerosis in patients with SLE; in one large study, both pediatric and adult patients with ESRD and SLE had significantly higher mortality due to cardiovascular disease than age-matched non-SLE patients with ESRD [36].…”
Section: Sle Specific Risk Factorsmentioning
confidence: 99%